Current approaches to treatment of patients with closed fractures of the patella - Yuriy D. Kim (Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics, 2021)
Abstract. Introduction Treatment of patients with acute fractures of the patella is the task of the trauma and orthopedic service and should provide restoration of the integrity of the bone tissue and the extensor apparatus of the knee joint for its early mobilization. There is an opinion that conservative treatment cannot meet requirements of patients’ quality of life, and therefore, most traumatologists are inclined to surgically treat patellar fractures. Purpose Based on the available literature data, to determine the most rational way to treat patients with patellar fractures Materials and methods Available studies published in the last 10 years were analyzed. The databases NCBI Pubmed, Healio Orthopedics, Medline were searched. Results Such osteosynthesis methods as patella suture, osteosynthesis with plates, special internal devices, external fixation devices, Kirschner wires and wire cerclage, various screws were covered. The question of clinical application of patellectomy was touched upon; the contribution of the Department of Traumatology, Orthopedics and Urgent Surgery of the Krasnov Samara State Medical University to the development of operative techniques of osteosynthesis of the patella, the basic concepts of scientific research, and also the most optimal ways of treating patients with patellar fractures were described. Conclusion The conservative method of treating patients with patellar fractures is most relevant if there are contraindications to surgery. It inevitably leads to persistent arthrogenic contracture. The best functional results of treatment have been achieved with surgical treatment due to the possibility of early mobilization of the knee joint. According to the data of available studies, plates and screws as well as osteosynthesis with Kirschner wires and wiring cerclage show maximum stability. There is evidence of a direct correlation between the risk of developing infectious complications and pain in the postoperative period and the number of elements of subcutaneous metal implants. Thus, the most optimal way to treat closed fractures of the patella is osteosynthesis with the use of wires and wire cerclage according to the tension band principle.